A Systematic Review and Meta-Analysis of Medical Students' Perspectives on the Engagement in Research. Issue 28 (July 2015) - Naing, Cho; Wai, Victor Nyunt; Durham, Jo; Whittaker, Maxine A.; Win, Ni Ni; Aung, Kyan; Mak, Joon Wah; Leischik., Roman
<x xml:space="preserve">Abstract</x> Abstract Engaging students in active learning lies at the center of effective higher education. In medical schools, students' engagement in learning and research has come under increasing attention. The objective of this study was to synthesize evidence on medical students' perspectives on the engagement in research. We performed a systematic review and meta-analysis. Relevant studies were searched in electronic databases. The methodological quality of the included studies was assessed. Overall, 14 observational studies (with 17 data sets) were included. In general, many studies did not use the same questionnaires and the outcome measurements were not consistently reported; these presented some difficulties in pooling the results. Whenever data permitted, we performed pooled analysis for the 4 education outcomes. A Bayesian meta-analytical approach was supplemented as a measure of uncertainty. A pooled analysis showed that 74% (95% confidence interval [CI]: 1.57%–11.07%; I2: 95.2%) of those students who engaged in research (while at the medical school) had positive attitudes toward their research experiences, whereas 49.5% (95% CI: 36.4%–62.7%; I2: 93.4%) had positive attitudes toward the study of medical sciences, 62.3% (95% CI: 46.7%–77.9%; I2: 96.3%) had self-reported changes in their practices, and 64% (95% CI: 30.8%–96.6%; I2: 98.5%) could have published their work. There was substantial heterogeneity among studies. We acknowledged the caveats and the merit of the current review. Findings showed that engagement in research resulted in favorable reactions toward research and academic learning. Future well-designed studies using standardized research tools on how to engage students in research are recommended.